A randomized controlled trial of a targeted support program for informal caregivers in adult psychiatry - Rexhaj, Shyhrete; Martinez, Debora; Golay, Philippe; Coloni-Terrapon, Claire; Monteiro, Shadya; Buisson, Leslie; Drainville, Anne-Laure; Bonsack, Charles; Ismailaj, Alban; Nguyen, Alexandra; Favrod, Jérôme (Frontiers in Psychiatry, 2023)
The importance of informal caregivers for persons with severe mental illness has been demonstrated. However, this role may cause a high care burden that considerably affects caregiver health. The Ensemble program is a five-session brief individual intervention designed to support informal caregivers. This trial aimed to assess the efficacy of the program versus SAU (support as usual) for participants with a high care burden.Methods: A single-center randomized controlled trial including 149 participants was conducted. Caregivers in the intervention arm participated in the Ensemble program. The effects of the intervention were assessed using mixed models for repeated measures analysis of variance on improvements in informal caregivers' psychological health status, optimism levels, burden scores, and quality of life at three time points (T0=pretest; T1=posttest at 2 months, and T2=follow-up at 4 months).Results: Analysis of the Global Psychological Index showed no significant effect at the two endpoints in favor of the Ensemble group. However, the Brief Symptom Inventory-Positive Symptom Distress Index was significantly lower at the two-month follow-up. A significant reduction in burden on the Zarit Burden Interview was observed post-intervention, along with an increase in optimism levels on the Life Orientation Test-Revised at follow-up in the Ensemble group. No significant differences were observed in quality of life. Clinical improvements in both psychological health status and burden levels were also identified.The Ensemble program offers an inclusive approach based on a recovery perspective that significantly reduces symptom distress and burden and increases optimism among informal caregivers.